Fibre optic hydrogen sensing for long term use in explosive environments - Chowdhury, S. A. (Cranfield University, 2015)
Hydrogen is an explosive and flammable gas with a lower explosive limit of just 4% volume in air. It is important to monitor the concentration of hydrogen in a potentially hazardous environment where hydrogen may be released as a by-product in a reaction or used as a principal gas/liquid. A fibre optic based hydrogen sensor offers an intrinsically safe method of monitoring hydrogen concentration. Previous research studies have demonstrated a variety of fibre optic based techniques for hydrogen detection. However the long-term stability of the hydrogen sensor and interrogation system has not yet been assessed and is the focus of this study. In the case of sensor heads being permanently installed in-situ, they cannot be removed for regular replacement, making long-term stability and reliability of results an important feature of the hydrogen sensor. This thesis describes the investigation and characterisation of palladium coated fibre optic sensor heads using two designs of self-referenced refractometer systems with the aim of finding a system that is stable in the long term (~6 months). Palladium was the chosen sensing material owing to its selective affinity for absorbing hydrogen. Upon hydrogen absorption, palladium forms a palladium- hydride compound that has a lower refractive index and lower reflectivity than pure palladium. The refractometers measured the changes in the reflectivity to enable calculation of the concentration of hydrogen present. A low detection limit of 10ppm H2 in air was demonstrated, with a response time of 40s for 1000ppm H2 in air. A further aspect to sensor stability was investigated in the form of sensor heads that had a larger area for palladium coverage. Hydrogen induced cracking in palladium is a common failure mechanism. A hypothesis is presented that a larger sensor area can reduce the probability of catastrophic failure resulting from cracks, which may improve the predictability of the sensor’s performance. Two sensor head designs have been proposed – fibre with a ball lens at the tip and fibre with a GRIN lens at the tip, both of which potentially offer a larger area than the core of a singlemode optical fibre. The limit of detection and response times of the sensor heads were characterised in hydrogen. For long term stability assessment of the sensor head and the interrogation unit, the system was left running for a period of 1 to 4 weeks and the noise and drift in the system was quantified using an Allan deviation plot.